UJI EFEKTIVITAS EKSTRAK DAUN TREMBESI (SAMANEA SAMAN) SEBAGAI LARVASIDA PADA LARVA AEDES AEGYPTI - Rizki Perdani; Hajrah Hidriya; Risnawati Risnawati (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Eradicating the larvae is one of the vector controls for Aedes aegypti. One alternative way to eradicate the larvae is by using vegetable insecticides (WHO, 1997 in Basri and Farasda, 2019). This study aims to determine the effectiveness of trembesi leaf extract (Samanea saman) as a larvicide on Aedes aegypti larvae. This study used an experimental design in the laboratory with trembesi leaves which were extracted using the maceration method for 4 days (96 hours) using a 96% ethanol solvent. The extract concentrations used were 0.1%, 0.5%, 1%, 5% and 10%. Each treatment contained 20 Aedes aegypti mosquito larvae and was observed every 24 hours and 48 hours. Based on the results of the exploratory test on the effectiveness of trembesi leaves (Samanea saman) against Aedes aegypti larvae with concentrations of 0.1%, 0.5%, 1%, 5%, and 10% which were observed for 24 hours and 48 hours, the results showed that the extract trembesi leaves (Samanea saman) with concentrations of 5% and 10% could kill all larvae populations within 24 hours, while concentrations of 0.5% and 0.1% could kill all larvae within 48 hours. Effectiveness of Trembesi Leaf Extract (Samanea saman) which affects the concentration factor with the most effective concentration at a concentration of 5% which can kill 100% of Aedes aegypti larvae within 24 hours.